INTEGRATING ESG PRACTICES IN PRIVATE HIGHER LEARNING EDUCATION FOR FINANCIAL SUSTAINABIL-ITY - Salin, Ahmad Saiful Azlin Puteh; Roslan Abd Wahab , Roslan x (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The landscape of higher education is undergoing a profound transformation, with private institutions, in particular, navigating a complex and competitive environment. In this context, ensuring long-term financial sustainability has emerged as a paramount concern. This theoretical paper intends to discuss the concept of financial sustainability and underscore its critical importance for private higher learning education, drawing a comparative analysis with public institutions. This paper will then recommend Environmental, Social, and Governance (ESG) principles as a strategic imperative for achieving this sustainability, outlining the general tenets of ESG and its application in an organisational context. Finally, this paper highlights the key underexplored issues at the intersection of ESG and the financial viability of private higher education, setting the stage for the research problem this paper seeks to address.